Tendency of Economic Crime in The use of Artificial Intelligence against Online Single Submission Risk based Approach in Sukoharjo Regency - Rahayu Subekti; Dandy Ramadhan (Proceeding International Conference Restructuring and Transforming Law, 2025)
The implementation of business licensing has been regulated in government regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing, however the use of the online single submission risk-based approach system in reality causes many problems including collusion and abuse of the authority of the verifier team's access rights which will cause investment realization becomes undirected and there are elements of criminal acts. This matter uses the Empirical Juridical method. In implementing the online business licensing system, the single submission risk-based approach is contrary to Law No. 28 of 1999 concerning State Administration that is Clean and Free from Corruption, Collusion and Nepotism. In conclusion, regarding Artificial Intelligence in public services, it should prioritize good governance that is accountable, not merely in the capacity to take advantage or enter into malicious conspiracy or collusion with those who have the authority to access rights.